Sensory, rheology, tribology and shelflife of reduced fat mayonnaise-type emulsions formulated with lipid-modified maize starch as fat replacer - Emmambux, Mohammad Naushad (University of Pretoria, 2024)
Thesis (PhD (Food Science))--University of Pretoria, 2019.